The role of self-awareness in avoiding unethical behavior in the workplace - Jebur, Ali Abdzaid; Saleh, Muhannad Karim; Idan, Ahmed Kadhim (Technium Business and Management, 2024)
The current research aims to demonstrate the role of self-awareness, an independent variable represented by self-evaluation, self-confidence, self-reflection, and emotional awareness, in avoiding unethical behaviors in the workplace, a dependent variable represented by misuse of time and resources, theft, bribery and corruption, and withdrawal. The descriptive analytical approach was adopted to present the theoretical aspect of the research, as well as to analyses and interpret the obtained data. We used the questionnaire as the primary tool to collect data from the Musayyib Technical Institute in Babylon, the research organization, and randomly selected a sample of 122 to retrieve the data. We selected 84 questionnaires for analysis and used the SPSS programme to test the hypotheses and verify their validity. We discovered that self-awareness plays a significant role in preventing unethical behaviors in the workplace.